Land reflection seismic, hydrogeological and magnetic study of an area prone to quick-clay landslides in southwest Sweden - Salas Romero, Silvia; Malehmir, Alireza; Snowball, Ian; Dessirier, Benoît (Uppsala University, 2019)
Quick-clay landslides are common geohazards in Nordic countries and Canada. The presence of potential quick clays is confirmed using geotechnical investigations, but near-surface geophysical methods, such as seismic and resistivity surveys, can also help identifying coarse-grained materials associated to the development of quick clays. We present the results of four reflection seismic profiles next to the Göta River in Sweden, along which many quick-clay landslide scars exist. An extensive coarse-grained layer exists in the sedimentary sequence and is interpreted and modeled in a regional context. Hydrological modeling of the coarse-grained layer is performed. Magnetic data are also studied within this investigation.

Four reflection seismic profiles collected in 2013 (line 5 has two parts, cabled geophones and wireless stations).

Jordskred av snabblera är vanliga "geohazards" i Norden och Kanada. Närvaron av potentiella snabbleror bekräftas med hjälp av geotekniska undersökningar, men geofysiska metoder i närheten av ytan, såsom seismiska och resistivitetsundersökningar, kan också bidra till att identifiera grovkornigt material i samband med utvecklingen av snabba leror. Vi presenterar resultaten av fyra reflexions-seismiska profiler bredvid Göta-floden i Sverige, längs vilka många jordskred av snabblera finns. Ett omfattande grovkornigt lager finns i sedimentärsekvensen och tolkas och modelleras i ett regionalt sammanhang. Hydrologisk modellering av det grovkorniga skiktet utförs. Magnetiska data studeras också inom denna undersökning.
Land reflection seismic, hydrogeological and magnetic study of an area prone to quick-clay landslides in southwest Sweden
Keywords: landslides; jordskred; Hydrology; Hydrologi; ELECTRIC/MAGNETIC FIELD EXPOSURE; SEISMIC PROFILE; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap